PKM-PENINGKATAN KETERAMPILAN GURU MATEMATIKA SMK KABUPATEN MAJENE DALAM PENGGUNAAN GEOENZO SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA - Syamsuddin Syamsuddin; Herlina Ahmad; Lili Hasliana; Abdul Latif; Nurfaida Tasni (LP4MK STKIP PGRI Lubuklinggau, 2020)
There are 30 math teachers at SMK in Majene Regency, from 10 public and private schools. Based on the results of discussions with the Mathematics MGMP of SMK in Majene Regency, which is a forum for mathematics teachers to carry out activities that can improve the competence of SMK mathematics teachers in Majene Regency. Data obtained from the use of mathematics applications have not been optimally carried out by teachers, this is due to the inability of teachers to use mathematics applications in the learning process. This is contrary to the era of technology like today, many free math software that can help teachers explain mathematical concepts. GeoEnzo is a free math software that can be used as a medium for learning mathematics. GeoEnzo makes it easy for teachers to display flat images and shapes and of course makes it easier for teachers to convey mathematical concepts. The methods used in this PkM are Forum Group Discussion (FGD) lectures, training and mentoring. The implementation phase of PkM includes (1) coordination and analysis of proposed needs, (2) compiling and validating the GeoEnzo module, (3) training in using GeoEnzo, (4) mentoring in the class using GeoEnzo, (5) evaluation and (6) reporting on the implementation of activities. The results of the analysis of the questionnaire before and after training and mentoring activities for the use of GeoEnzo as a learning medium, obtained skills in using GeoEnzo increased from 0% to 100%.